Phylogeography and sex-biased dispersal across riverine manatee populations (Trichechus inunguis and Trichechus manatus) in South America. - Paula Satizábal; Antonio A Mignucci-Giannoni; Sebastián Duchêne; Dalila Caicedo-Herrera; Carlos M Perea-Sicchar; Carmen R García-Dávila; Fernando Trujillo; Susana J Caballero (PLoS ONE, 2012)
Phylogeographic patterns and sex-biased dispersal were studied in riverine populations of West Indian (Trichechus manatus) and Amazonian manatees (T. inunguis) in South America, using 410bp D-loop (Control Region, Mitochondrial DNA) sequences and 15 nuclear microsatellite loci. This multi-locus approach was key to disentangle complex patterns of gene flow among populations. D-loop analyses revealed population structuring among all Colombian rivers for T. manatus, while microsatellite data suggested no structure. Two main populations of T. inunguis separating the Colombian and Peruvian Amazon were supported by analysis of the D-loop and microsatellite data. Overall, we provide molecular evidence for differences in dispersal patterns between sexes, demonstrating male-biased gene flow dispersal in riverine manatees. These results are in contrast with previously reported levels of population structure shown by microsatellite data in marine manatee populations, revealing low habitat restrictions to gene flow in riverine habitats, and more significant dispersal limitations for males in marine environments.